Management of giant condyloma acuminatum on HIVAIDS patients with limited healthcare facilities - Stanley Ariestia Tanjaya; Flora Debby Ngolo; Wahyu Setyo Nugroho (Neurologico Spinale Medico Chirurgico, 2020)
Giant Condyloma Acuminatum (GCA) or Buschke-Lowenstein Tumour (BLT) is a unique variant of condyloma acuminatum. The incidence of this disease tends to increase due to the increasing prevalence of Human Immunodeficiency Virus (HIV) infection. Until now, there is no therapeutic guideline for GCA, and many therapeutic options are not available for one in limited healthcare facilities. We present one case of GCA in HIV-positive women treated in health centers with limited facilities in a rural area. We treat the patient by doing a sitz bath with povidone-iodine 1%, simple excision with electrocautery for the tumour, adequate analgetics, regular wound care, and zinc supplementation acts as immunotherapy. Complications of wound infection by candida caused the lengthy hospitalization of the patient. After discharge, the patient came for control every week; no other lump arises again, and the wound was getting better. A combination of conservative and surgical treatment followed by regular wound care can lead to a good result in the GCA case, even with minimal healthcare facilities.